The effect of special exercises on according to some aspects of attention in developing the skillful performance of young football players (Journal of the College of Basic Education, 2022)
The study aimed to prepare exercises according to some aspects of attention in developing the skillful performance of young soccer players in Maysan governorate, as well as the effect of these exercises on the rate of skill development. Foot in Maysan governorate for the sports season (2018-2019) and the number of (20) players, and the duration of the study was from (6/15/2019) to (1/25/2020 AD), and the researcher used the appropriate statistical means for the sample of the study and the results. The details, most notably the use of the correlation coefficient of Pearson, the computational mean, the T-value and other statistical means mentioned in the study, the researcher intended to present, analyze and discuss the results of the study in light of the statistical scores of the players in the pre and posttests of the research sample and for the experimental and control groups, and concluded The researcher said that the exercises prepared by the researcher affected the research sample and the experimental group positively, as well as a rate of improvement in skill performance, and the researcher recommended the adoption of special exercises in the educational curricula Training and training for young football players and interest in special exercises because they help the development of skillful performance, as well as concern for the psychological and educational aspect of the players by adopting these exercises or designing exercises that are compatible with the age group of football players .